PENGUATAN PERAN KELUARGA DALAM PELAKSANAAN PENDIDIKAN AGAMA ISLAM SEBAGAI UPAYA PEMBENTUKAN GENERASI BERAKHLAK MULIA - Arestya Saksitha, Deassy; Rahmawati, Hesti; Rahmayani Mutmainnah, Inayah; Hikmah, Nurul; Amalia, Rachel; Rahayu, Silvia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the role of the family in Islamic education as the primary environment for shaping children's character, spirituality, and moral values. The study aims to analyze the role of the family in Islamic education, identify the factors that support and hinder it, and examine efforts to strengthen family involvement in children's Islamic learning. This research employs a qualitative library research method, reviewing relevant books, journals, and scholarly sources on family and Islamic education. The findings indicate that the family is the primary educational institution responsible for instilling faith, worship practices, noble character, and Islamic values in children. Several factors support the success of Islamic education within the family, including parental guidance, affection, religious role modeling, and a positive family environment. Conversely, obstacles include limited parental religious knowledge, work-related busyness, negative technological influences, unfavorable peer environments, and family conflicts. To optimize Islamic education, parents need to strengthen religious literacy, provide exemplary behavior, establish effective communication, cultivate religious habits, and collaborate with schools and the wider community. Therefore, the family plays a crucial role in developing a generation with strong faith, noble character, intellectual competence, and social responsibility in accordance with Islamic teachings.